Seagull - Harper, Kathryn (Cambridge : Cambridge University Press, 2016)
Pep and Lin find a dirty Seagull, how can they help? In Red Band illustrations continue to support understanding but readers also need to use decoding skills. Slightly longer texts with less repetition extend high-frequency word knowledge. Contains full teaching support including learning outcomes, curriculum links and follow-up activities.
Keywords: English - fiction; Gulls - Juvenile - fiction